RIGHT SIDED DIVERTICULITIS MIMICKING ACUTE APPENDICITIS: A CASE REPORT AND REVIEW OF ONE-YEAR BARIUM ENEMAS FOR LOCATION OF DIVERTICULOSIS - PANTONGRAG-Brown, Linda; CHANSUE, Ekwan (The ASEAN Journal of Radiology, 2023)
Right-sided diverticulitis is an uncommon cause of acute abdomen. We present a case of right-sided diverticulitis, whose presentation mimics acute appendicitis. We also review the prevalence of diverticulosis in our hospital, which shows that right-sided diverticulosis is very common, found in about 66% of diverticulosis cases. Because of high incidence of right-sided diverticulosis in our region, awareness of right-sided diverticulitis is important, since the treatment for this condition is mostly nonsurgical, which is opposite to acute appendicitis.